PENDEKATAN KONSELING KOGNITIF PERILAKU DENGAN TEKNIK COGNITIVE RESTRUCTURING UNTUK MENINGKATKAN KEPERCAYAAN DIRI TERHADAP KORBAN PELECEHAN SEKSUAL - Crisfatika Yulianti; Ameliya Sayyidatus Syifa'; Nailah Hadi Paramita; Anita Dhuwi Rahayu; Ari Khusumadewi; Devi Ratnasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Cognitive restructuring techniques in cognitive-behavioral counseling are methods that aim to help people identify, challenge, and change negative or illogical thoughts into more positive and realistic ways of thinking. These techniques help change the way of thinking that influences feelings and actions, making them very beneficial for individuals who have had traumatic experiences, including those who have experienced sexual abuse and feel insecure. This study aims to examine the application of cognitive restructuring techniques in improving the self-confidence of students who are victims of sexual abuse by looking at changes in thinking and emotional responses during counseling. The method used in this study is qualitative with semi-structured in-depth interviews, which provide an opportunity for counselees to share their experiences, fears, and irrational beliefs resulting from trauma. The interviews were conducted in several sessions to gather in-depth, rich information that reflected gradual cognitive changes. This article discusses the background of the problem, an explanation of cognitive restructuring techniques, step-by-step counseling procedures, analysis of counseling results, and the role of counselors in helping clients change their way of thinking. The results of the analysis show that the application of cognitive restructuring techniques is effective.